PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN NIRA SAWIT KAMPUNG MAREDAN BARAT KECAMATAN TUALA - Dwi Larasanti; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research uses the theory of Ambar Teguh S (2004: 83), the stages that must be passed include the stage of awareness and behavior formation, the stage of transformation of abilities, the stage of increasing intellectual abilities. This study uses a qualitative method with an ethnographic approach. The informants in this study were the government of West Maredan Village, palm oil farmer groups and the people of West Maredan Village. Informants were taken using snowball sampling. Data collection was carried out by observation, interviews, documentation and literature study. Data analysis used a linear and hierarchical approach. The results showed that community empowerment in the management of palm oil is still going well. Then the supporting factors for community empowerment are having superior commodities, support from the local government. The inhibiting factors for community empowerment are decreasing community participation and inadequate supporting technology in the village. This is what hampers community empowerment in managing palm sap into brown sugar.Keywords: Empowerment, Community, Management.